Analysis of Principal Supervision In the Development of PJOK Teacher Competence - Yoga Nugraha; Muhammad Nur Alif; Aam Ali Rahman; Ayi Suherman (Universitas Negeri Semarang, 2026)
This research aims to analyze the practice of academic supervision carried out by school principals with non-linear educational backgrounds (non-PE) in developing the competence of Physical Education (PE) teachers at junior high schools (SMP) in Sumedang Regency. Supervision is a key instrument for keeping the quality of learning at a high level, however, the application of supervision in PE is often limited by the technical limitations of supervisors in grasping the substance of movement and sports pedagogy in the field. Qualitative data were obtained through case study designs, through in-depth interviews, observations and documentation studies in schools that have the characteristics of urban and rural areas. The results of the analysis processed by NVivo software indicate that principal supervision is organized in four main dimensions, namely, planning, implementation, interaction dynamics, and performance impact. The findings suggest that while supervision contributes positively to the development of teachers’ pedagogical and professional competencies, its effectiveness is still limited by the dominance of one-way communication, overly generalized assessment instruments and a lack of sustainable follow-up. This study points to the need for a more collaborative and adaptive approach to clinical supervision to close the technical competency gap between principals and teachers . The novelty of this study is to provide a substantive assessment model to enable non-linear supervisors to still be able to promote teacher professionalism without need of profound technical expertise in sports.